2014
DOI: 10.1186/1471-2334-14-164
|View full text |Cite
|
Sign up to set email alerts
|

Children of Senegal River Basin show the highest prevalence of Blastocystissp. ever observed worldwide

Abstract: BackgroundBlastocystis sp. is currently the most common intestinal protist found in human feces and considered an emerging parasite with a worldwide distribution. Because of its potential impact in public health, we reinforced the picture of Blastocystis sp. prevalence and molecular subtype distribution in Africa by performing the first survey of this parasite in Senegal.MethodsStool samples from 93 symptomatic presenting with various gastrointestinal disorders or asymptomatic children living in three villages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
165
2
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(185 citation statements)
references
References 57 publications
(125 reference statements)
13
165
2
5
Order By: Relevance
“…In both instances, infants are Blastocystis negative compared to a high carriage rate in the adult population (Pandey et al, 2015) (Scanlan et al, unpublished). Conversely, in a recent study of 93 children living in the Senegal River Basin, 100% were Blastocystis positive (El Safadi et al, 2014). Interestingly, eight of the nine positives within the adult group were male.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both instances, infants are Blastocystis negative compared to a high carriage rate in the adult population (Pandey et al, 2015) (Scanlan et al, unpublished). Conversely, in a recent study of 93 children living in the Senegal River Basin, 100% were Blastocystis positive (El Safadi et al, 2014). Interestingly, eight of the nine positives within the adult group were male.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is considerable variation in prevalence rates between different populations; for example, recent reports have given positive prevalence rates of anywhere between ~24-100% for different populations living in Europe, the Middle East, India and Africa (AbuOdeh et al, 2016;Alfellani et al, 2013;Bart et al, 2013;El Safadi et al, 2014;Krogsgaard et al, 2015;Pandey et al, 2015;Scanlan and Stensvold, 2013;Scanlan et al, 2014). With respect to Blastocystis transmission to humans, three distinct modes of transmission have been proposed (Tan, …”
Section: Introductionmentioning
confidence: 99%
“…15,16 Using PCR technique, the highest prevalence of Blastocystis infection was found among children of Senegal River Basin, which was 100%. 17 In this study, direct wet smear and in vitro cultivation were used as screening detection methods. Every fecal sample was cultured in Jones' medium to detect Blastocystis sp., which increased Blastocystis sp.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Its prevalence considerably varies between geographic areas, reaching 100% in developing countries and 56% in industrialized ones. 3,4 Poor health care and hygiene can explain these differences between countries since its main transmission mode is the fecal-oral route through the consumption of contaminated food or water. 1 It has also been shown that prevalence data may depend on detection methods, especially direct-light microscopy (DLM) of fecal smears versus polymerase chain reaction (PCR) assays.…”
mentioning
confidence: 99%